Assessment of the Relationship between Hypnotics and Delirium Using the Japanese Adverse Drug Event Report (JADER) Database - Imai, Toru; Yoshida, Yoshikazu; Hazama, Katsuyuki; Kikuchi, Norikazu; Suzuki, Shinichiro; Hidaka, Shinji (YAKUGAKU ZASSHI, 2018)
The Japanese Adverse Drug Event Report (JADER) database was used to examine the risk of delirium and the time of its onset with various hypnotics, including 10 benzodiazepines (BZDs), 3 non-benzodiazepines (non-BZDs), 1 melatonin receptor agonist (MRTA), and 1 orexin receptor inhibitor (OXRI). Data entered in the JADER database between April 1, 2004 and February 1, 2016 were analyzed. The index for safety signal detection, the reporting odds ratio (ROR), was the odds ratio for adverse drug reaction reporting. The ROR for each drug was calculated; a signal was considered present if the lower bound of the 95% confidence interval of the ROR was greater than 1. The time to onset of delirium was calculated for drugs for which the number of days from the start of drug administration to delirium onset was reported. During the period examined in the analysis, a total of 621114 adverse drug reaction reports were seen, and the total number of delirium reports was 1417 after redundant cases were excluded. A signal was detected for 5 of the 10 BZDs and all 3 non-BZDs, with no signal for the MRTA and the OXRI. The time of delirium onset varied widely even for drugs classified as being in the same action duration group, and no correlation was seen for delirium onset time. The results of this study suggested that delirium risk varies depending on the hypnotic. Thus, hypnotics can be selected according to their delirium risk.